Konsep Khulu’ Perspektif Syekh Zainuddin Al-Malibari Dalam Kitab Fiqh Fathul Mu’in - Muhammad Sauqi; Yulianti Yulianti; Iqrimah Bailany Azmi (SPT. haria Journal and Education Center Publishing, 2026)
Khulu’ is a form of divorce in Islamic law that grants a wife the right to dissolve her marriage by providing compensation (iwadh) to her husband. This study aims to analyze the concept of khulu’ from the perspective of Sheikh Zainuddin al-Malibari in the book Fathul Mu’in, as well as to examine its legal status and requirements. This research employs a library research method with a qualitative approach and descriptive-analytical analysis. The primary data source is the book Fathul Mu’in, while secondary sources are gathered from various relevant Islamic legal literature. The findings indicate that, according to Sheikh Zainuddin al-Malibari, khulu’ is positioned as a sharia-based mechanism that carries ethical, social, and justice dimensions designed to protect women’s rights when a marriage can no longer achieve the goals of sakinah, mawaddah, and rahmah. Legally, khulu’ possesses a dynamic and contextual nature, with statuses ranging from mubah (permissible when there is genuine disharmony), haram (forbidden when done without valid reasons or due to coercion/injustice by the husband), to sunnah (recommended when the husband fails to fulfill religious obligations). The concept of khulu’ in Fathul Mu’in demonstrates that Islam provides realistic and equitable solutions to marital problems. Khulu’ is not merely a dissolution of the relationship, but an instrument to prevent greater harm while adhering to the principles of morality, ethics, and the best interests of both parties.